Variations Among Primary Care Physicians in Exercise Advice, Imaging, and Analgesics for Musculoskeletal Pain: Results From a Factorial Experiment. Issue 1 (January 2014) - Maserejian, Nancy N.; Fischer, Michael A.; Trachtenberg, Felicia L.; Yu, Jing; Marceau, Lisa D.; McKinlay, John B.; Katz, Jeffrey N.
<x xml:space="preserve">Abstract</x> Objective To examine whether medical decisions regarding evaluation and management of musculoskeletal pain conditions varied systematically by characteristics of the patient or provider. Methods We conducted a balanced factorial experiment among primary care physicians in the US. Physicians (n = 192) viewed 2 videos of different patients (actors) presenting with pain: undiagnosed sciatica symptoms or diagnosed knee osteoarthritis. Systematic variations in patient gender, socioeconomic status, and race and physician gender and experience (<20 versus ≥20 years in practice) permitted estimation of unconfounded effects. Analysis of variance was used to evaluate associations between patient or provider attributes and clinical decisions. Quality of decisions was defined based on the current recommendations of the American College of Rheumatology, American Pain Society, and clinical expert consensus. Results Despite current recommendations, less than one‐third of physicians would provide exercise advice (30.2% for osteoarthritis and 32.8% for sciatica). Physicians with fewer years in practice were more likely to provide advice on lifestyle changes, particularly exercise (P ≤ 0.01), and to prescribe nonsteroidal antiinflammatory drugs for pain relief, both of which were appropriate and consistent with current recommendations for care. Newer physicians ordered fewer tests, particularly basic laboratory investigations or urinalysis. Test ordering decreased as organizational emphasis on business or profits increased. Patient factors and physician gender had no consistent effects on pain evaluation or treatment. Conclusion Physician education on disease management recommendations regarding exercise and analgesics and implementation of quality measures may be useful, particularly for physicians with more years in practice.